Peri-procedural use of rivaroxaban in elective percutaneous coronary intervention to treat stable coronary artery disease - Vranckx, Pascal; Leebeek, Frank W. G.; Tijssen, Jan G. P.; Koolen, Jacques; Stammen, Francis; Herman, Jean-Paul R.; de Winter, Robbert J.; van t Hof, Arnout W. J.; Backx, Bianca; Lindeboom, Wietze; Kim, So-Young; Kirsch, Bodo; van Eickels, Martin; Misselwitz, Frank; Verheugt, Freek W. A. (Thrombosis and Haemostasis, 2015)
Patients on rivaroxaban requiring percutaneous coronary intervention (PCI) represent a clinical conundrum. We aimed to investigate whether rivaroxaban, with or without an additional bolus of unfractionated heparin (UFH), effectively inhibits coagulation activation during PCI. Stable patients (n=108) undergoing elective PCI and on stable dual antiplatelet therapy were randomised (2:2:2:1) to a short treatment course of rivaroxaban 10 mg (n=30), rivaroxaban 20 mg (n=32), rivaroxaban 10 mg plus UFH (n=30) or standard peri-procedural UFH (n=16). Blood samples for markers of thrombin generation and coagulation activation were drawn prior to and at 0, 0.5, 2, 6–8 and 48 hours (h) after start of PCI. In patients treated with rivaroxaban (10 or 20 mg) and patients treated with rivaroxaban plus heparin, the levels of prothrombin fragment 1 + 2 at 2 h post-PCI were 0.16 [0.1] nmol/l (median) [interquartile range, IQR] and 0.17 [0.2] nmol/l, respectively. Thrombin–antithrombin complex values at 2 h post-PCI were 3.90 [6.8] μg/l and 3.90 [10.1] μg/l, respectively, remaining below the upper reference limit (URL) after PCI and stenting. This was comparable to the control group of UFH treatment alone. However, median values for thrombin–antithrombin complex passed above the URL with increasing tendency, starting at 2 h post-PCI in the UFH-alone arm but not in rivaroxaban-treated patients. In this exploratory trial, rivaroxaban effectively suppressed coagulation activation after elective PCI and stenting.Clinical trial registration: Clinical Trials.gov Identifier: NCT01442792 URL: EudraCT. Unique identifier: No: 2011–001094–58.
Keywords: Anticoagulation; coronary artery disease; rivaroxaban; thrombosis